PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN SEPEDA MOTOR HONDA DI KABUPATEN JEMBER - Reiga Ritomiea Ariescy; Diah Yulisetiarini; Mohammad Dimyati (RELASI : JURNAL EKONOMI, 2017)
This research aims to examine the effect of price and product quality on customer satisfaction and Honda motorcycles customer loyalty in Jember District. The research design used was confirmatory research. The population of this study is all customers of Honda motorcycles in Jember District. The samples arre 115 respondents. Respondents were taken using non probability sampling technique with purposive sampling approach. Analytical tool used is Structural Equation Modeling (SEM). The model used in the research is quite good because it has met 7 of 8 measurements of Goodness of Fit. The results of this study prove that product quality has a significant positive effect on customer loyalty. Product quality also has a significant positive effect on customer loyalty. Price has positive effect insignificant to customer satisfaction. Price also positively insignificant to customer loyalty Customer satisfaction has no positive influence on customer loyalty.